PERSEPSI MASYARAKAT SETU BABAKAN TERHADAP PERKAMPUNGAN BUDAYA BETAWI DALAM UPAYA MELESTARIKAN KEBUDAYAAN BETAWI - Priarti Megawanti (Universitas Indraprasta PGRI, 2015)
Culture is a reflection of the personality of a nation. Therefore, if the people had no longer pretend their culture, they would lose their personality as the core of Jakarta residents who took part increasing the development of Jakarta. Culture can be form as ideas (custom or norm), activities (exemplified in the form of day-to-day tradition), and art. The people that living in the area Setu Babakan, directly or indirectly, be a mover and supporter of the Betawi’s culture that was raised in the Perkampungan Budaya Betawi. Therefore, society's perception of the Betawi’s culture is important to be explored more deeply, because society that determines whether or not the Betawi’s culture took place. All of it depends on the perception of the communities on the Betawi’s culture. Keywords: Perception, culture, Betawi